Mastering Visual Studio 2022 Develop Apps Like a Pro with Advanced Visual Studio Techniques Using C# and .NET - Dabadie, Romain Ottonelli (Packt Publishing, Limited, 2024)
Mastering Visual Studio, one of the fastest and most comprehensive integrated development environments (IDEs), is crucial for building efficient, scalable, and modern apps. Written by a seasoned technical expert in .NET with over a decade of experience, Mastering Visual Studio 2022 helps you leverage the full capabilities of this powerful IDE. Packed with step-by-step guidance and self-assessment tools, this book adopts a practical approach to helping you advance your Visual Studio expertise. You'll explore complex topics such as debugging, testing, extension development, and CI/CD, and gain practical insights to enhance your skills. The book covers advanced coding analysis and refactoring techniques that will help improve code quality and maintainability. You'll also get to grips with Visual Studio's capabilities for multi-platform development; integrating machine learning models; and cloud development with Azure, AWS, and Google Cloud. You'll master Git workflows, conflict resolution, and DevOps practices with GitHub Actions and Azure DevOps, ensuring seamless team collaboration and efficient deployment pipelines. By the end of this book, you'll have become proficient in Visual Studio 2022, as well as being able to craft your own customized experience and confidently create robust, high-quality applications.
Description based upon print version of record
Keywords: Microsoft Visual studio; Microsoft .NET Framework; C# (Computer program language); Internet programming; Web site development